(untitled) (Iter, 2022)
Tha author claims that truth is a matter o f rather little concern within human existence. The search o f truth is actually the scope o f scientific and logical thought; but art and poetry, as well as human action, individual or collective, do not aim at truth and have other ends. As for i(religious truths ”, they are, strictly speaking, beliefs, not truths, since, in spite o f their meaning for human beings, they do not share the features o f truth, being unprovable and not subject to the principies o f contradiction or o f sufficient reason.